PERANCANGAN PROSES BISNIS HUMAN RESOURCE MANAGEMENT (HRM) BERBASIS DIAGRAM BUSINESS PROCESS MODEL AND NOTATION (BPMN) - Arisanti, Diah; Marisa, Fitri (DINAMIKA DOTCOM, 2018)
Human Resource Management (HRM) system at PT. RetGoo Sentris Informa is currently still not using a special application that is well structured. So it is necessary to design a new Human Resource Management (HRM) business process system with the aim to improve employee performance in the Human Resource Director (HRD) division in terms of time and efficiency. The design stages used include designing business process diagrams, variables, and interface design. So as to facilitate the design of HRM business processes. This design has the benefit of being a reference for creating HRM (Human Resource Management) applications so that they are more structured. In Designing HRM Business processes based on BPMN diagrams at PT. RetGoo Sentris Informa, what is needed is a BPMN diagram to design the business processÂ Keywoard â HRM, BP